Comparison of the 2019 European Alliance of Associations for Rheumatology/American College of Rheumatology Systemic Lupus Erythematosus Classification Criteria With Two Sets of Earlier Systemic Lupus Erythematosus Classification Criteria. Issue 9 (14th July 2021) - Petri, Michelle; Goldman, Daniel W.; Alarcón, Graciela S.; Gordon, Caroline; Merrill, Joan T.; Fortin, Paul R.; Bruce, Ian N.; Isenberg, David; Wallace, Daniel; Nived, Ola; Ramsey‐Goldman, Rosalind; Bae, Sang‐Cheol; et al.
Abstract : Objective: The Systemic Lupus International Collaborating Clinics (SLICC) 2012 systemic lupus erythematosus (SLE) classification criteria and the revised American College of Rheumatology (ACR) 1997 criteria are list based, counting each SLE manifestation equally. We derived a classification rule based on giving variable weights to the SLICC criteria and compared its performance to the revised ACR 1997, the unweighted SLICC 2012, and the newly reported European Alliance of Associations for Rheumatology (EULAR)/ACR 2019 criteria sets. Methods: The physician‐rated patient scenarios used to develop the SLICC 2012 classification criteria were reemployed to devise a new weighted classification rule using multiple linear regression. The performance of the rule was evaluated on an independent set of expert‐diagnosed patient scenarios and compared to the performance of the previously reported classification rules. Results: The weighted SLICC criteria and the EULAR/ACR 2019 criteria had less sensitivity but better specificity compared to the list‐based revised ACR 1997 and SLICC 2012 classification criteria. There were no statistically significant differences between any pair of rules with respect to overall agreement with the physician diagnosis. Conclusion: The 2 new weighted classification rules did not perform better than the existing list‐based rules in terms of overall agreement on a data set originally generated to assess the SLICC criteria. Given the added complexity of summing weights, researchers may prefer the unweighted SLICC criteria. However, the performance of a classification rule will always depend on the populations from which the cases and non‐cases are derived and whether the goal is to prioritize sensitivity or specificity.